Kisah teladan orang-orang saleh / Abdul aziz Nashir Al-Jalil; alih bahasa, Ikhwanuddin; editor, Firman Arifian - AL-JALIL, Abdul Aziz Nashir; Ikhwanuddin; Firman Arifian (Istanbul, 2015)
246 hlm. : ilus. ; 23 cm.